Association of vitamin C with the risk of age‐related cataract: a meta‐analysis. (4th March 2015) - Wei, Lin; Liang, Ge; Cai, Chunmei; Lv, Jin
Abstract: Purpose: Whether vitamin C is a protective factor for age‐related cataract remains unclear. Thus, we conducted a meta‐analysis to summarize the evidence from epidemiological studies of vitamin C and the risk of age‐related cataract. Methods: Pertinent studies were identified by searching in PubMed and in Webscience. The random effect model was used to combine the results. Meta‐regression and subgroups analyses were used to explore potential sources of between‐study heterogeneity. Publication bias was estimated using Egger's regression asymmetry test. Results: Finally, 15 articles with 20 studies for vitamin C intake and eight articles with 10 studies for serum ascorbate were included in this meta‐analysis. The relative risk (RR) and 95% confidence interval of cataract for the highest versus the lowest category of vitamin C intake was 0.814 (0.707–0.938), and the associations were significant in America and Asia. Significant association of cataract risk with highest versus the lowest category of serum ascorbate was found in general [0.704 (0.564–0.879)]. Inverse associations were also found between serum ascorbate and nuclear cataract and posterior subcapsular cataract. Conclusions: Higher vitamin C intake and serum ascorbate might be inversely associated with risk of cataract. Vitamin C intake should be advocated for the primary prevention of cataract.